PENGHUNIAN KAMAR HOTEL DARI SEGI FASILITAS, ONLINE TRAVEL AGENT DAN CUSTOMER SERVICE (STUDI PADA GRAND AMBARRUKMO HOTEL YOGYAKARTA) - Susiyanto Susiyanto; Nur Rohman (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2022)
The aim of this research is to empirically prove the influence of personal selling, product quality and price on the decision of sellers of koala skewers in Yogyakarta partially and simultaneously. The problem in the research that the researchers did was whether personal selling, product quality and price decisions were made by the koala skewer seller in Yogyakarta. Either partially or jointly and to find out which factors are more dominantly influencing. The population used is all hotel customers at the time the research was conducted and 100 people were taken as samples. This study uses a questionnaire as a tool to obtain data about the effect of facilities, online travel agents and customer service on hotel occupancy rates. based on the analysis using SPSS 25.0 for windows. The data analysis technique uses multiple linear regression analysis which serves to prove a research hypothesis. The results showed that simultaneously the variables of Facility, Online Travel Agent and Customer Service had an effect on hotel occupancy rates, partially personal selling variables, product quality and price on seller satisfaction.Keywords: Room Occupancy, Facilities, Online Travel Agent and Customer Service